2016
DOI: 10.1002/btpr.2368
|View full text |Cite
|
Sign up to set email alerts
|

Effect of green and red light in lipid accumulation and transcriptional profile of genes implicated in lipid biosynthesis in Chlamydomonas reinhardtii

Abstract: Microalgae have the potential to accumulate triacylglycerols under different light spectra. In this work, Chlamydomonas reinhardtii was grown under white (400-700 nm), red (650 nm), and green (550 nm) lights. According to our results, red light (650 nm) has a positive effect in the microalgae growth and chlorophyll concentration. About the lipid content, the control culture (white light-illuminated) reached a 4.4% of dry cell weight (dcw), whereas the culture grown at 550 nm showed an increase of 1.35-fold in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 47 publications
1
6
0
1
Order By: Relevance
“…Similarly, Atta et al [48] found that the lipid content of C. vulgaris increased when the light intensity with blue LED lamps increased from 100 to 200 µmol photons m −2 s −1 at 12:12 h light: dark. Gaytán-Luna et al [58] studied the effect of green, white, and red light on the lipid content of Chlamydomonas reinhardtii. They found that the maximum lipid content was observed when cultivated at red light in comparison with cultivation at white and green light.…”
Section: Experiments In the Closed Bioreactor-effect Of Wavelength Anmentioning
confidence: 99%
“…Similarly, Atta et al [48] found that the lipid content of C. vulgaris increased when the light intensity with blue LED lamps increased from 100 to 200 µmol photons m −2 s −1 at 12:12 h light: dark. Gaytán-Luna et al [58] studied the effect of green, white, and red light on the lipid content of Chlamydomonas reinhardtii. They found that the maximum lipid content was observed when cultivated at red light in comparison with cultivation at white and green light.…”
Section: Experiments In the Closed Bioreactor-effect Of Wavelength Anmentioning
confidence: 99%
“…In our previous work, the expression profile of the BCX1 and ACP1 genes in C. reinhardtii cultures exposed to red (650 nm) and green (550 nm) light were down‐regulated when compared with white light (control experiment); while the acyl‐ACP thiolase ( FAT1 ) and acyl‐sn‐glycerol‐3‐phosphate acyltransferase (PLS1) genes were up‐regulated under red light with respect to green light . According to this, the gene expression profile implicated in the early steps of the fatty acid synthesis may be impacted differently according to the stress conditions.…”
Section: Discussionmentioning
confidence: 90%
“…The reaction mixture in a total volume of 10 μL contained 100 ng of total cDNA, 5 μL of SYBRGreen Master Mix reagent (Applied Biosystems, Mulgrave, Australia), and 100 nM of each primer. The oligonucleotides sequences used in this study were previously described . RT‐PCR conditions were 10 min at 95°C, followed by 40 cycles of 15 s at 95°C (denaturation), 30 s at 60°C (primer annealing), and 30 s at 60°C (primer extension).…”
Section: Methodsmentioning
confidence: 99%
“…For the production of ATP and NADPH and the synthesis of particles needed for growth, algae need light of appropriate wavelength and color temperature [45][46][47]. It would seem that since the light intensity improves the growth rate of the algae, the bioreactors should be illuminated as intensely as possible.…”
Section: Type Of Photobioreactor Modelmentioning
confidence: 99%